Adrenal haemorrhage as a complication of COVID-19 infection. Issue 11 (30th November 2020) - Sharrack, Noor; Baxter, Conal Thomas; Paddock, Michael; Uchegbu, Elizabeth
Abstract : We report an unusual complication of COVID-19 infection in a 53-year-old Caucasian man. He presented with shortness of breath, fever and pleuritic chest pain. A CT pulmonary angiogram (CTPA) demonstrated acute bilateral pulmonary embolism and bilateral multifocal parenchymal ground glass change consistent with COVID-19 (SARS-CoV-2) infection. Right adrenal haemorrhage was suspected on the CTPA which was confirmed on triple-phase abdominal CT imaging. A short Synacthen test revealed normal adrenal function. He was treated initially with an intravenous heparin infusion, which was changed to apixaban with a planned outpatient review in 3 months' time. He made an uncomplicated recovery and was discharged. Follow-up imaging nearly 5 months later showed near complete resolution of the right adrenal haemorrhage with no CT evidence of an underlying adrenal lesion.